Experimental investigation of CuO/Sio2 hybrid nano-lubricant in R600a vapour compression refrigeration system. (2021) - Senthilkumar, A.; Abhishek, P.V.; Adithyan, M.; Arjun, A.
Highlights: The influence of CuO and Sio2 hybrid nanolubricants in R600a system. Reduction in energy consumed by compressor. Enhancement in Coefficient of performance and refrigeration effect. Abstract: Vapour compression refrigeration systems is the most common methods adopted around the world. Besides, being one of the popular refrigeration systems it has been improvised over the period aiming towards increased coefficient of performance. Among various factors, energy demand has been one the major issues in vapor compression refrigeration system that is being addressed from different perspectives. Introduction of new materials in more prominent structure in lubricants is one major path to a solution for increasing the C.O.P of the system. In this project Cuo/Sio2 nano-lubricants are used as a substitute for pure mineral oil in vapor compression refrigeration system. Hybrid nano-lubricants obtained by dispersing two different nano-particles namely CuO and Sio2 at 0.2 g/L and 0.4 g/L concentrations and refrigerant mass charges of 40and 60 g of R600a refrigerant are being experimented in this research. CuO and Sio2 hybrid nano-lubricants leads to improvement in Coefficient of performance by 35%, Cooling capacity by 18% and resulted in reduced compressor power consumption of 75 W compared to system without nanolubricants. With the experimentation results the performance of nano-lubricant is compared with base lubricant .The results revealed that R600a refrigeration system with nano-lubricants performed better compared to base lubricant in with respect to coefficient of performance, cooling capacity, pull down time and compressor power consumption. It will lead to energy efficient vapour compression refrigeration system.